2000
DOI: 10.1128/mcb.20.22.8571-8579.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 Promotes Cell Survival by Stimulation of Dynein Light Chain Expression and Inhibition of Neuronal Nitric Oxide Synthase Activity

Abstract: oxide synthase (nNOS), thereby reducing nNOS activity. Furthermore, nNOS expression and activity were significantly increased in differentiated PC12 cells after NGF withdrawal. This increased nNOS activity as well as increased nNOS dimer after NGF withdrawal were inhibited by COX-2 or DLC/PIN overexpression. An nNOS inhibitor or a membrane-permeable superoxide dismutase (SOD) mimetic protected differentiated PC12 cells from NGF withdrawal apoptosis. In contrast, NO donors induced apoptosis in differentiated PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 57 publications
(66 reference statements)
3
53
0
Order By: Relevance
“…This was not unexpected, since p21 cip-1 protects against p53-mediated apoptosis (30). Moreover, COX-2 is a survival factor by suppressing caspase-3 activity (31) or inhibiting NO-and superoxide-mediated apoptosis (32). Thus, COX-2 might exclusively influence the growth suppressing properties of p53 in our cell system.…”
Section: Discussionmentioning
confidence: 94%
“…This was not unexpected, since p21 cip-1 protects against p53-mediated apoptosis (30). Moreover, COX-2 is a survival factor by suppressing caspase-3 activity (31) or inhibiting NO-and superoxide-mediated apoptosis (32). Thus, COX-2 might exclusively influence the growth suppressing properties of p53 in our cell system.…”
Section: Discussionmentioning
confidence: 94%
“…One function is the modulation of nNOS catalytic activity to prevent deleterious overproduction of NO. Indeed, it has been reported that a cyclooxygenase-induced increase of PIN expression is, through an inhibition of the production of superoxide and NO by nNOS, able to prevent nerve growth factor-deprived PC12 cells from apoptosis (37). Concerning pancreatic ␤-cells, PIN overexpression resulted in a clear increase in insulin secretion, bearing evidence that this highly conserved protein plays a role in the stimulus-secretion coupling of the ␤-cell.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 has been reported to inhibit nerve growth factor withdrawal apoptosis in differentiated PC12 cells (28). A different study found that an apoptosisrelated gene, dynein light chain (DLC), was up-regulated in PC12 cells by COX-2 expression or PGE 2 treatment (29). DLC expression prevented apoptosis of PC12 cells by reducing neuron nitric-oxide synthase activity.…”
Section: Discussionmentioning
confidence: 99%